Quaternarized pdppz: Synthesis, DNA-binding and biological studies of a novel dppz derivative that causes cellular death upon light irradiation - Williams, David; Gunnlaugsson, Thorfinnur; Cloonan, Suzanne (My University, 2011)
The quaternarized pdppz derivative 1 was shown to bind strongly to DNA with concomitant changes in its ground and excited state photophysical properties. Furthermore, the compound also showed rapid cellular uptake, and induced apoptosis upon light irradiation in various cancer cell lines after 24 hours of incubation.
PUBLISHED
Keywords: quaternarized pdppz derivative 1; dppz derivative; cellular death; apoptosis; Cancer